Muhammadiyah as Policy Entrepreneur in Policy Change Making of Oil and Gas Law - Kurniawati, Nawang; Hadna, Agus Heruanto; Kurniawan, Bachtiar Dwi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Muhammadiyah pursues a policy agenda by suing Law Number 21 of the Year 2001 regarding the oil and gas in 2012. Muhammadiyah acts as PE, bringing together three streams of MSA (problem stream, politic stream, and policy stream) to open the policy window and make the public issues (lawsuit) of the policy agenda. Therefore, this study intends to analyze the efforts of Muhammadiyah as a policy entrepreneur in policy change making towards oil and gas law. This research is used a descriptive qualitative method to describe the chronology of Muhammadiyah as a policy actor. The purposive sampling method was used for this study because it involved informants who understood the problem. This study also uses data collection techniques by interview, literature study, and documentation analyzed using Miles and Huberman's analysis technique. As the result of this research, Muhammadiyah came as an informal policy actor interested in pursuing policy ideas. The stream of a problem and political current rose as the most defining currents for Muhammadiyah to become a policy entrepreneur. The two streams succeeded in influencing the policy flow, and those were able to bring together three MSA. Hence, this lawsuit had implications for Migas's dissolution based on MK Decision Number 36/PUU-X/2012.